Bibliometric analysis of global research trends on small-cell lung cancer (2012–2021) - Wang, Kai; Zhang, Han; Li, Xin; Ding, Yun; Li, Jiuzhen; Wang, Zixiao; Liu, Xin; Sun, Shuai; Sun, Daqiang (Frontiers in Oncology, 2022)
Background: Small-cell lung cancer (SCLC) is a recalcitrant tumor with a poor prognosis. With the rise of SCLC research in the past decade, this study aims to analyze the foundation and frontiers of SCLC research through bibliometric analysis. Methods: Relevant publications from the Web of Science Core Collection were retrieved on January 3, 2022. R package bibliometrix and EXCEL2019 were used to analyze quantitative variables. Bibliometric mapping was constructed by VOS viewer and CiteSpace software to visualize citation, co-authorship, co-occurrence, and co-citation analysis of countries/regions, organizations, authors, references, and keywords. Results: A total of 2,361 publications related to SCLC were identified with the total amount of articles steadily increasing, where China is the most productive country with 859 papers. Scholars and organizations from the United States, China, and Europe are primary sources of this research, among which the University of Texas MD Anderson Cancer Center made the most contribution to the field with 122 papers. Lung Cancer published the highest number of SCLC-related articles with a total of 121, while the Journal of Thoracic Oncology received the most citations totaling 3,098. Rudin, Charles M., and Sage, Julien are the most creative author. Leora, Horn, 2018, New Engl J Med and Rudin, Charles M., Nat Genet, 2012 can be categorized as classic literature owing to their high citations or strong sigma value. "Heterogeneity & Subtypes" and "Immunotherapy" may be the new frontiers in the SCLC domain. Conclusion: Research on SCLC showed an upward trend based on the current global situation. Moreover, the current scope of collaboration in SCLC research is chiefly regional, which should further focus on transnational cooperation in the future. More attention should be devoted to "Heterogeneity & Subtypes" and "Immunotherapy", which will be the hotspots in future research.